Kinsey - Condon, Bill 1955-.; Fox Searchlight Pictures; Qwerty Films (Firm).; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. Twentieth Century Fox Home Entertainment, 2005)
A portrait of a man driven to uncover the most private secrets of the nation, and journey into the mystery of human behavior. His 1948 book Sexual behavior in the human male irrevocably.
Originally released as a motion picture in 2004.
Special features: Full-length audio commentary by writer/director, Bill Condon.
Performers, Liam Neeson, Laura Linney, Chris O'Donnell, Peter Sarsgaard, Timothy Hutton, John Lithgow, Tim Curry, OliverPlatt.
DVD videos, region 1.
Keywords: Sexual ethics -- Drama; Sexologists -- Drama; Sexology -- Research -- Drama